Gugatan Rekonvensi: Disparitas Antara Ketentuan Normatif Hukum Acara Perdata dan Praktik Peradilan dalam Penyelesaian Sengketa Wanprestasi (Studi Putusan Nomor 146/Pdt.G/2022/PN Srg) - Anugrah, Rizky; Wardani, Yulia Kusuma; Rusmawati, Dianne Eka; Rohaini, Rohaini; Febrianto, Dita (SENTRI: Jurnal Riset Ilmiah, 2026)
A land Sale and Purchase Binding Agreement (PPJB) frequently gives rise to default (wanprestasi) disputes resolved through litigation. In a reciprocal agreement, allegations of default may arise from both directions, giving the defendant an interest in filing a counterclaim (rekonvensi). This study analyses the implementation of the counterclaim in resolving the default dispute in Decision Number 146/Pdt.G/2022/PN Srg and highlights the disparity between the normative rules of civil procedure and judicial practice regarding the connexity requirement of a counterclaim. The study employs a normative juridical method with statutory, case, and conceptual approaches. The results show that the counterclaim satisfied the formal requirements because it was filed together with the answer (Article 132b HIR in conjunction with Article 158 paragraph (1) RBg) and was closely connected to the principal claim as both derived from PPJB Number 75 over the same object, without violating the prohibitions in Article 132a HIR. Although Article 132a HIR and Supreme Court Circular Number 7 of 2012 do not require connexity, judicial practice treats connexity as a decisive requirement, as shown by a comparison with Decision Number 288/Pdt.G/2021/PN.Jkt.Utr, in which the counterclaim was declared inadmissible. This disparity should be corrected by affirming connexity as a binding guideline grounded in the principles of civil procedure.